Solutions with peculiarities of one equation of mathematical physics - Gutlyansky , V. Ya.; Ryazanov , V. I.; Гутлянский , В. Я.; Рязанов , В. И. (Institute of Mathematics, NAS of Ukraine, 1992)
A theorem for the representation of solutions with singularities of logarithmic type of a certain equation of mathematial physics in terms of quasiconformal mappings is obtained.